2004
DOI: 10.1113/jphysiol.2003.052068
|View full text |Cite
|
Sign up to set email alerts
|

Glycine rectifies vascular dysfunction induced by dietary protein imbalance during pregnancy

Abstract: Protein restriction in rat pregnancy programmes the development of elevated systolic blood pressure and vascular dysfunction in the offspring. A recent study has shown that hypertension is reversed by maternal glycine supplementation. Whether this protective effect is exerted directly on the embryo and fetus, or indirectly via effects on the mother, is unknown although we have previously shown abnormalities in the maternal vasculature. We tested the hypothesis that dietary glycine repletion would reverse endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(87 citation statements)
references
References 43 publications
3
84
0
Order By: Relevance
“…In humans, the TDH pathway accounts for only 7-11% of threonine oxidation [16] in adults whereas up to 44% of oxidation is through this pathway in preterm infants [24]. Glycine is also important during gestation in rodents [25] and even a small increase in the conversion of threonine to glycine may lead to a considerable increase in the demand because of the high glycine flux. However in a preliminary experiment where animals were infused with [U-14 C] threonine on d21 of gestation, we were unable to detect any radioactivity in serum or intracellular glycine pools (Rees and Palmer unpublished results).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, the TDH pathway accounts for only 7-11% of threonine oxidation [16] in adults whereas up to 44% of oxidation is through this pathway in preterm infants [24]. Glycine is also important during gestation in rodents [25] and even a small increase in the conversion of threonine to glycine may lead to a considerable increase in the demand because of the high glycine flux. However in a preliminary experiment where animals were infused with [U-14 C] threonine on d21 of gestation, we were unable to detect any radioactivity in serum or intracellular glycine pools (Rees and Palmer unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…[25,[29][30][31]. It is becoming clear that a disturbance in maternal metabolism lies at the centre of these changes and a perturbation of amino acid metabolism may be an important mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…11 Supplementation of low protein diets with glycine or folate reverses the programming effect of those diets. 12,13 However such a mechanism may lack gene specificity, whereas other data argues that it is specific genes that are susceptible to this effect. 14 -17 Thus in this study we set out to test the hypothesis that alteration of DNA methylation of 1 or more RAS component genes might underlie the alteration of gene expression that culminated in the development of hypertension.…”
mentioning
confidence: 89%
“…Several maternal dietary co-factors have also been shown to prevent the development of hypertension in offspring of MLP dams although the mechanisms are not well established. Maternal supplementation with glycine [140,141] , folic acid [142,143] and choline (authors unpublished observations) has been shown to prevent programming-induced elevations in systolic blood pressure in offspring in postnatal life. There is some evidence for an epigenetic basis to these observations utilizing dietary methyl donor and co-factor supplementation; clinically relevant reductions in specific dietary inputs to the methionine/folate cycles during the periconceptional period can lead to widespread epigenetic alterations to DNA methylation in offspring and modify adult health-related phenotypes [107,115] .…”
Section: Critical Windows Of Development and Avenues For Interventionmentioning
confidence: 99%